Estudo de aplicabilidade da nutrição de precisão na diversidade de uma produção de suínos em crescimento e terminação - Fraga, Bruno Neutzling (2014)
The objective of this study was to model and evaluate the performance, supply and requirements of nutrients and tissue deposition to pigs in growing and finishing phases in production scenarios (CP), to adjust the diet program phases. Six CP were selected in the northwest region in Rio Grande do Sul between August and November in 2012 to collect the data. The amount of 2,200 animals followed a pre established program of six diets (sequential and quantitative) through the historical and productive farms index or standard profile animal (PAP) and the feeding program was ad libitum. The performance data collections in CP were held in randomly selected pens and they were used throughout the experimental period. The collected data were modeled based on an animal average to feature each profile animal with animal performance bends and nutritional requirements in PAP and in the six CP. The animals were housed at 65 ± 7 days old and weighing 22.11 ± 1.41kg and were slaughtered at 159 ± 10 days old and weighing 121.18 ± 7kg. The CP average was higher than 0.27kg on consumption and 0.12kg on weight gain according to the standard profile animal (PAP). The average daily demand of Digestible Lysine and Net Energy (LysD:EN) estimated at PAP was 3,18 ± 0,16g.Mcal-1 and 3,81g.Mcal-1 of supply in CP. The average predicted to protein deposition of 153 ± 25g.day-1 at PAP underestimated in 16 ± 10g.day-1 the CP. The average lipid deposition of CP was higher by 54 ± 26g.day-1 at PAP. Diet and food programs at PAP generated 17.9% excess of LysD:EN, the adjustment reduced it to 8,5%. While adjusting the phases, Initial and Growth I diets had not been consumed, there was a reduction of 111.7% to Growth II diet, 57.2% to Finishing I diet and there was an increase of 53,6% to Growth III diet and 49.6% to Finishing III diet. The phases adjustment promoted a corn reduction of 43.78kg and protein sources reduction of 16.65kg per animal. The real production scenarios show differences between performance, supply and demands of nutrients which modeling is able to describe and compare the effects of tissue deposition. This way, it is possible to determine adjustments for the best moment in phases transition and reduce the nutrients requirement.